A PIAS1 Protective Variant S510G Delays polyQ Disease Onset by Modifying Protein Homeostasis. Issue 4 (23rd December 2021) - Lee, Yan Hua; Tsai, Yu‐Shuen; Chang, Che‐Chang; Ho, Chun‐Chen; Shih, Hsiu‐Ming; Chen, Hui‐Mei; Lai, Hsing‐Lin; Lee, Chia‐Wei; Lee, Yi‐Chung; Liao, Yi‐Chu; Yang, Ueng‐Cheng; Cheng, Tzu‐Hao; et al.
Abstract: Background: Polyglutamine (polyQ) diseases are dominant neurodegenerative diseases caused by an expansion of the polyQ‐encoding CAG repeats in the disease‐causing gene. The length of the CAG repeats is the major determiner of the age at onset (AO) of polyQ diseases, including Huntington's disease (HD) and spinocerebellar ataxia type 3 (SCA3). Objective: We set out to identify common genetic variant(s) that may affect the AO of polyQ diseases. Methods: Three hundred thirty‐seven patients with HD or SCA3 were enrolled for targeted sequencing of 583 genes implicated in proteinopathies. In total, 16 genes were identified as containing variants that are associated with late AO of polyQ diseases. For validation, we further investigate the variants of PIAS1 because PIAS1 is an E3 SUMO (small ubiquitin‐like modifier) ligase for huntingtin (HTT), the protein linked to HD. Results: Biochemical analyses revealed that the ability of PIAS1 S510G to interact with mutant huntingtin (mHTT) was less than that of PIAS1 WT, resulting in lower SUMOylation of mHTT and lower accumulation of insoluble mHTT. Genetic knock‐in of PIAS1 S510G in a HD mouse model (R6/2) ameliorated several HD‐like deficits (including shortened life spans, poor grip strength and motor coordination) and reduced neuronal accumulation of mHTT. Conclusions: Our findings suggest that PIAS1 is a genetic modifier of polyQ diseases. The naturally occurring variant, PIAS1 S510G, is associated with late AO in polyQ disease patients and milder disease severity in HD mice. Our study highlights the possibility of targeting PIAS1 or pathways governing protein homeostasis as a disease‐modifying approach for treating patients with HD. © 2021 International Parkinson and Movement Disorder Society Abstract : PIAS1 is a genetic modifier associated with late onset of polyQ diseases. The naturally occurring PIAS1 S510G variant interacts with mutant huntingtin (mHTT) poorly, resulting in a lower SUMOylation and accumulation of mHTT. Knock‐in of PIAS1 S510G ameliorates major symptoms of Huntington's disease in mice, supporting its protective role.